Kemitraan Puskesmas dan Sekolah dalam Pencegahan Malaria pada Anak Usia Sekolah di Seluma Bengkulu - Hilza Novrinda; Misnaniarti Misnaniarti; Rostika Flora; HM Zulkarnain; Samwilson Samwilson; Risnawati Tanjung (Jurnal Promosi Kesehatan Indonesia, 2020)
Background: The partnership between Puskesmas (Community Health Center) and school to improve the health of school-age children known as the Trias school health unit. In Seluma only 7.69% of schools have a room for health school program. This study aims to explore the partnership between Puskesmas’ and schools in malaria prevention to school-age children in Seluma. Method: This study used qualitative research with phenomenological approach. It was conducted in April 2019. The main informants consisted of 5 teachers, from 5 elementary schools and 2 UKS staff Puskesmas from Puskesmas Puguk and Puskesmas Talang Tinggi, who have worked over than three years. The data collected by indepth interview, FGDs and observation. Results: The role of the UKS Puskesmas staffs was not optimal in carrying out the triad UKS activities. They only carry out routine UKS activities. Partnership between Puskesmas and schools has not been implemented optimally. It is still very limited action to cooperate the routine triad implementation from the Puskesmas and schools. A review needs to be done to assess the performance of the UKS, especially through healthy school competition activities.